Mastering Vocabulary with Flashcards: Unveiling Their Impact on Learning - Fitri Harianingsih; Hastini Hastini (Journal of General Education and Humanities, 2023)
This research aimed to discover how using flashcards affected seventh-grade SMP Negeri 2 Toili students' vocabulary growth. The research design used quantitative research. The researcher employed a complete sampling approach to choose the sample. A sample of 42 students was chosen for this research. The research conducted pre- and post-tests to collect data. According to the Paired Sample Statistics table, the average student score for the experimental class is equivalent to the post-test results, which are 86.67 points greater than the pre-test result of 64.76. Given that the significance (2-tailed) value is known to be between 0.001 and 0.05, H0 is refused, whereas H1 is approved. The fact that there was a distinction between the pre- and post-tests indicates that employing flashcards to increase vocabulary among seventh-graders at SMP Negeri 2 Toili had an impact.